What is Robotic Surgery and Is It Safe? An Academic Review for the Digital Health Era - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
What is Robotic Surgery and Is It Safe? An Academic Review for the Digital Health Era Introduction The integration of advanced technology into medicine ...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Patient Care; Machine Learning